Correction to: A Dynamic Optimization Approach for Solving Spine Kinematics While Calibrating Subject-Specific Mechanical Properties - Wang, Wei; Wang, Dongmei; Falisse, Antoine; Severijns, Pieter; Overbergh, Thomas; Moke, Lieven; Scheys, Lennart; De Groote, Friedl; Jonkers, Ilse (Annals of biomedical engineering, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s10439-021-02791-2